Safety and Multi-employer Worksites in High-risk Industries: An Overview - Nygren, Magnus; Jakobsson, Mats; Andersson, Eira; Johansson, Bo (Relations industrielles / Industrial Relations, 2017)
This paper focuses on safety on multi-employer worksites in high-risk industries. Relevant industries are those that utilize flexible labour arrangements and specialization, such as construction, mining and petroleum production, and that traditionally have been high-risk due to hazards in the physical work environment and the occurrence of unsafe work processes and practices. These industries also share common characteristics in matters of overall work environments, multi-employer worksites (including subcontracting chains), as well as tasks performed by contractors, making it relevant to explore and clarify the situation regarding the safety of the affected groups. A comprehensive review is performed of 43 peer-reviewed research articles published up until early 2015, with a main focus on international studies covering safety issues on multi-employer worksites in construction and industrial work settings such as mining, petroleum production and manufacturing.The results show that previous research has focused on a number of key issues that may be divided into three broad categories: 1- contract work characteristics; 2- structural/organizational factors and conditions; 3- cultural conditions. Much of the focus is on structure and organization, for example, how multi-employer arrangements can lead to breakdowns in communication and overall disorganization effects in relation to safety. There is, however, a need for further studies on the nature of these structural and organizational factors and conditions, such as focused studies on the consequences of power asymmetry for the ability of contractors to adhere to safety laws and regulations. Furthermore, we argue that the development towards blurred organizational boundaries in these networks due to extensive outsourcing and long-term contracts may be a worthwhile avenue for future research into safety on multi-employer worksites.